2013
DOI: 10.1016/j.jbiosc.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clostridium ljungdahlii DSM 13528 reference genes in gene expression studies by qRT-PCR

Abstract: Clostridium ljungdahlii DSM 13528 is a promising platform organism for biofuel production from syngas. Gene expression analysis permits a better understanding of the important molecular biological characteristics of this organism, such as carbon fixation and solvent adaptation. Normalization is a prerequisite for accurate gene expression analysis, but until now, no valid reference genes have been proposed for quantitative real-time polymerase chain reaction (qRT-PCR) analysis of C. ljungdahlii DSM 13528. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The difference in activities for anaerobic cultures of these closely related species can be explained by autotrophic growth for C. ragsdalei versus mixotrophic growth, with fructose as the predominant carbon substrate for C. ljungdahlii. As previously mentioned, expression of C. ljungdahlii's main tungsten-containing AOR (CLJU_c20110) was significantly less for fructose-grown cells than for 80%-CO-grown cells (93,94). Despite the lower activity of molybdenum-containing AORs, their benefit of a higher tolerance to oxidized compounds like O 2 , NOx, and SOx may make this predicted molybdenum-containing AOR a more interesting genetic target for overexpression in commercial applications where less syngas purification means higher margins.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The difference in activities for anaerobic cultures of these closely related species can be explained by autotrophic growth for C. ragsdalei versus mixotrophic growth, with fructose as the predominant carbon substrate for C. ljungdahlii. As previously mentioned, expression of C. ljungdahlii's main tungsten-containing AOR (CLJU_c20110) was significantly less for fructose-grown cells than for 80%-CO-grown cells (93,94). Despite the lower activity of molybdenum-containing AORs, their benefit of a higher tolerance to oxidized compounds like O 2 , NOx, and SOx may make this predicted molybdenum-containing AOR a more interesting genetic target for overexpression in commercial applications where less syngas purification means higher margins.…”
Section: Discussionmentioning
confidence: 71%
“…Prior to this study, Kopke et al predicted that under surplus reducing equivalents, acetate could be converted to acetaldehyde, the precursor of ethanol, by the AORs encoded by CLJU_c20110 and CLJU_c20210 (2). It was also shown that CLJU_c20110 was significantly more highly expressed when C. ljungdahlii was grown autotrophically (80% CO, 20% CO 2 ) than when it was grown heterotrophically with fructose (93,94). In contrast, we observed that both CLJU_c20110 and CLJU_c20210 had relatively low transcript counts, which may be explained by the fact that the growth medium used in this study had fructose as the primary carbon source (Table 1).…”
Section: Discussionmentioning
confidence: 89%
“…The reference genes gyrA , fotl and rho [29] were not differentially expressed between the planktonic and the biofilm condition (results not shown), illustrating that the normalization between the different treatments was performed well. A total of 403 genes (9.4% of the genes of the C .…”
Section: Resultsmentioning
confidence: 99%
“…gyrA (CLAU_2078; encodes DNA gyrase subunit A) and rho (CLAU_2269; encodes transcriptional termination factor) were chosen as housekeeping genes because they exhibited the most stable gene expression levels for different carbon sources and stresses in closely related acetogen C. ljungdahlii DSM 13528 (Liu et al, 2013). The amplification efficiencies of the TaqMan probes and primers were empirically determined to be between 94.2% and 99.7% (R 2 ≥0.998) by constructing a standard curve using serially diluted cDNA as template (data not shown).…”
Section: Methodsmentioning
confidence: 99%